1978
DOI: 10.1063/1.324336
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion and solubility of iron in copper

Abstract: The chemical diffusion coefficients and the solubility limits of iron in copper were determined in the temperature range 650–1050 °C by electron probe microanalysis. Specimens were 99.999% copper single crystals. The diffusion is best described by two regression lines: DFe-Cu=0.504 exp(−49740/RT) cm2/s for the temperature interval 1050–800 °C and DFe-Cu=0.091 exp(−46140/RT) cm2/s for the temperature interval 800–650 °C. The solubility of iron in copper is given to logC=2.951−3357(1/T °K) wt% in the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 6 publications
2
27
2
Order By: Relevance
“…In the previous experiments the evaporated layer of a metal was rather thin: 4 μm of copper [6], 0.1 μm of copper [9] or 1.5-3 μm of iron [7]. Here, it is observed that thickness of interaction layer is even 50 μm (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In the previous experiments the evaporated layer of a metal was rather thin: 4 μm of copper [6], 0.1 μm of copper [9] or 1.5-3 μm of iron [7]. Here, it is observed that thickness of interaction layer is even 50 μm (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…1,2] and later [3][4][5][6][7][8]. It was observed, that diffusivities of elements is different in paramagnetic and ferromagnetic state; for example diffusivity of copper in polycrystalline iron is D Cu/Fe = 0.57exp(-57000/RT) (cm 2 /s) in temperature range 800-1050ºC and D Cu/Fe = 0.47exp(-58380/RT) (cm 2 /s) in temperature range 650-750ºC [9].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations